Miller & Freund's probability and statistics for engineers - Johnson, Richard Arnold (Prentice Hall, 2011)
This text is rich in exercises and examples, and explores both elementary probability and basic statistics, with an emphasis on engineering and science applications. Much of the data have been collected from the author's own consulting experience and from discussions with scientists and engineers about the use of statistics in their fields. In later chapters, the book emphasizes designed experiments, especially two-level factorial design.